2018
DOI: 10.4236/ojog.2018.85053
|View full text |Cite
|
Sign up to set email alerts
|

A Five-Year Survey of Uterine Fibroids at a Nigerian Tertiary Hospital

Abstract: Introduction: Uterine leiomyomas, commonly called fibroids are benign tumors of uterine myometrium composing of smooth muscle with variable amount of connective tissue and common gynecological problem among women of reproductive age. It is the commonest tumor of the female pelvic organ. Objective: To determine the incidence of uterine fibroids, socio-demographic, clinical characteristics and outcome of uterine leiomyoma management. (83.3%) had myomectomy, 23 (11.6%) had total abdominal hysterectomy and 9 (4.6%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 9 publications
2
20
2
Order By: Relevance
“…The commonest gynaecological diagnosis was uterine fibroid (33.7%) and this is higher than most figures reported in the Nigerian literatures of 6.4% to 13.5% [14][15][16][17][18]. This was followed by infertility (28.1%) which is higher than previous reports of 15.4% [4], 15.7% [7] and 23.9% [8], but lower than those in other studies of 32.0% [9] and 48.1% [10].…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…The commonest gynaecological diagnosis was uterine fibroid (33.7%) and this is higher than most figures reported in the Nigerian literatures of 6.4% to 13.5% [14][15][16][17][18]. This was followed by infertility (28.1%) which is higher than previous reports of 15.4% [4], 15.7% [7] and 23.9% [8], but lower than those in other studies of 32.0% [9] and 48.1% [10].…”
Section: Discussioncontrasting
confidence: 57%
“…Infertility and nulliparity are also associated with increased incidence of uterine fibroids [13]. It represents 6.4% of all gynaecological admissions in Abuja [14], 6.5% in Ile-Ife [15], 9.8% in Enugu [16], 10.7% in Nnewi [17] and 13.5% in Ilorin [18]. Fasubaa et al [19] found that about a quarter of women with infertility had symptomatic uterine fibroids and this represented about 35%-40% of the overall number of women presenting as uterine fibroid in their study.…”
Section: Introductionmentioning
confidence: 99%
“…Babah et al reported CS rate of 51.3% from a study conducted in a public tertiary health facility in Lagos, Nigeria [ 20 ]. Other authors working in public tertiary health facilities in Nigeria have reported varying CS rates such as 21.4% in Abuja [ 21 ], and 42.4% in Bayelsa [ 22 ]. Studies have suggested that CS rates are often higher in private health facilities compared to public health facilities [ 14 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence in Nigeria ranges from 17.9-26%, as against 5-11% reported in Europe and United States (Aboyeji et al, 2012). Further, uterine fibroid is responsible for 6.4% of all the gynaecological admissions and 21.35% of all major gynaecological surgeries in a tertiary teaching hospital in Nigeria (Isah, Adewole, Agida and Omonua, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Several risk factors responsible for fibroid include age, heritage, genes reproductive factors, sex hormones, obesity, lifestyle, environmental and infection (Olotu et al, 2008;McLucas, 2009;Yuan, Qiang, Shengyong, Liqiang, Guowei, Peiyu, 2013;Sparic, Mirkovic, Malvasi and Tinelli, 2015;Isah et al, 2018). In recent times, the complete absence of successful diagnosis, treatment and cure of fibroid worldwide has increased its risks among women (Khan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%